Measurement properties of the upright motor control test for adults with stroke: a systematic review. Issue 1 (December 2016) - Gorgon, Edward; Lazaro, Rolando
Abstract Background The Upright Motor Control Test (UMCT) has been used in clinical practice and research to assess functional strength of the hemiparetic lower limb in adults with stroke. It is unclear if evidence is sufficient to warrant its use. The purpose of this systematic review was to synthesize available evidence on the measurement properties of the UMCT for stroke rehabilitation. Methods Electronic databases that indexed biomedical literature were systematically searched from inception until October 2015 (week 4): Embase, PubMed, Web of Science, CINAHL, PEDro, Cochrane Library, Scopus, ScienceDirect, SPORTDiscus, LILACS, DOAJ, and Google Scholar. All studies that had used the UMCT in the time period covered underwent hand searching for any additional study. Observational studies involving adults with stroke that explored any measurement property of the UMCT were included. The COnsensus-based Standards for the selection of health Measurement INstruments was used to assess the methodological quality of included studies. The CanChild Outcome Measures Rating Form was used for extracting data on measurement properties and clinical utility. Results The search yielded three methodologic studies that addressed criterion-related validity and contruct validity. Two studies of fair methodological quality demonstrated moderate-level evidence thatKnee Extension andKnee Flexion subtest scores were predictive of community-level and household-level ambulation. One study of fair methodological quality provided limited-level evidence for the correlation ofKnee Extension subtest scores with a laboratory measure of ground reaction forces. No published studies formally assessed reliability, responsiveness, or clinical utility. Limited information on responsiveness and clinical utility dimensions could be inferred from the included studies. Conclusions The UMCT is a practical assessment tool for voluntary control or functional strength of the hemiparetic lower limb in standing in adults with stroke. Although different levels of evidence suggest that theKnee Extension andKnee Flexion subtests may possess criterion and construct validity, the lack of published literature examining content validity, reliability, and responsiveness raises questions regarding the use of the UMCT in routine clinical practice. These key findings highlight the need to further investigate the UMCT's measurement properties toward enhancing its standardization.